Prevalensi Kasus Persistensi Gigi Sulung di Poliklinik Gigi UPTD Puskesmas Baturiti I - Pramesti, Ketut Ayu; Pratama, I Wayan Agus Wirya (Jurnal Kesehatan Gigi (Dental Health Journal), 2025)
The problem of dental health in Indonesia is a complex issue and requires serious attention from various parties, including the government, health institutions, and society in general. Tooth persistence is a condition where primary teeth do not fall out at the right time as they should and remain in the mouth after teething. permanent should grow. The aim of the research is to determine the prevalence of chronic persistence in November 2023 – January 2024 at the UPTD Dental Polyclinic, Baturiti I Tabanan Health Center, Bali. Observational research method with a cross-sectional method. The results of the study showed that the number of visits by chronic periodontitis patients in November 2023 - January 2024 at the UPTD Dental Polyclinic, Baturiti I Tabanan Health Center, Bali was 165 patients out of a total of 896 patients, of which 74 were men (44.85%) and 91 were women. (55.15%). Conclusion: A total of 165 patients out of a total of 896 patients with the most cases of tooth persistence in January 2024 were 65 patients (21.17%). There were 91 female patients (55.15%) and were the dominant number, while there were 74 male patients (44.85%).